Relaciones entre parámetros ambientales y erosionabilidad en suelos de las comarcas de Ayora y Hoya de Buñol (Valencia) - Garcia-Fayos P.; Hernández J.-L.; Rubio J.-L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Relationship between soil erodibility values and several extrinsic factors type of soil, litology, vegetation cover, use and soil perturbation by forest fires were analysed through chi-squared tests of Independence and correspondence analysis. The factor showing the highest influence on erodibility values was type of soil and, in a perturbations by forest fires showed not pernicious effect on erodibility.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)